If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5-2x=8-4x
We move all terms to the left:
5-2x-(8-4x)=0
We add all the numbers together, and all the variables
-2x-(-4x+8)+5=0
We get rid of parentheses
-2x+4x-8+5=0
We add all the numbers together, and all the variables
2x-3=0
We move all terms containing x to the left, all other terms to the right
2x=3
x=3/2
x=1+1/2
| 2x^2+8x-5=8 | | 0=n^2-19/3n+2 | | x2−3x−18=10 | | 5=3f+2 | | 18-(3x-5)=5(x-1)-6 | | 2w+2(3w-5)=82 | | 4=-7x+8x | | X/3-2x+1/2=5/6 | | (2x+1)^2-(-x+1)^2=(x-1)(3x+2) | | -7p+8p=7 | | 0.02(y-9)+0.18y=0.14y-0.03(10) | | 48-3x=-109-8x | | 3x-5=5x/x-3/x | | -6(v-1)=5v-49 | | -281=1-6(5-6x) | | 10x-21=4x | | 7x-4;x=5 | | 8/9(54-36)+2=-3/4(-40+16x)+90x | | 12x+2=11x-6 | | 3x-5=5x-3/x | | 6(x+2)-4x=2(x-3)+18 | | -7y+23=-2(y-4) | | 2(y+7)=5(3-2y) | | x/9=11/5- | | 15+q#6=-21 | | X+2=x-7 | | 5x-6+3x=x | | 5(1-5x)=-28+2x | | 7x-112=3x+60 | | -8(w-1)=-4w+36 | | 4(2x-7)=6x | | -9x-45-10x-1=35 |